Widespread formation of cherts during the early Eocene climatic optimum - G. Muttoni; D. V. Kent (Palaeogeography, Palaeoclimatology, Palaeoecology, 2007)
Radiolarian cherts in the Tethyan realm of Jurassic age were recently interpreted as resulting from high biosiliceous productivity along upwelling zones in subequatorial paleolatitudes the locations of which were confirmed by revised paleomagnetic estimates. However, the widespread occurrence of cherts in the Eocene suggests that cherts may not always be reliable proxies of latitude and upwelling zones. In a new survey of the global spatio-temporal distribution of Cenozoic cherts in Deep Sea Drilling Project (DSDP) and Ocean Drilling Program (ODP) sediment cores, we found that cherts occur most frequently in the Paleocene and early Eocene, with a peak in occurrences at ∼50 Ma that is coincident with the time of highest bottom water temperatures of the early Eocene climatic optimum (EECO) when the global ocean was presumably characterized by reduced upwelling efficiency and biosiliceous productivity. Cherts occur less commonly during the subsequent Eocene global cooling trend. Primary paleoclimatic factors rather than secondary diagenetic processes seem therefore to control chert formation. This timing of peak Eocene chert occurrence, which is supported by detailed stratigraphic correlations, contradicts currently accepted models that involve an initial loading of large amounts of dissolved silica from enhanced weathering and/or volcanism in a supposedly sluggish ocean of the EECO, followed during the subsequent middle Eocene global cooling by more vigorous oceanic circulation and consequent upwelling that made this silica reservoir available for enhanced biosilicification, with the formation of chert as a result of biosilica transformation during diagenesis. Instead, we suggest that basin–basin fractionation by deep-sea circulation could have raised the concentration of EECO dissolved silica especially in the North Atlantic, where an alternative mode of silica burial involving widespread direct precipitation and/or absorption of silica by clay minerals could have been operative in order to maintain balance ...